Facilitators and barriers to the adoption of ergonomic solutions in construction. Issue 3 (March 2017) - Dale, Ann Marie; Jaegers, Lisa; Welch, Laura; Barnidge, Ellen; Weaver, Nancy; Evanoff, Bradley A.
Abstract : Background: Rates of musculoskeletal disorders in construction remain high. Few studies have described barriers and facilitators to the use of available ergonomic solutions. This paper describes these barriers and facilitators and their relationship to the level of adoption. Methods: Three analysts rated 16 proposed ergonomic solutions from a participatory ergonomics study and assessed the level of adoption, six adoption characteristics, and identified the category of adoption from a theoretical model. Results: Twelve solutions were always or intermittently used and were rated positively for characteristics of relative advantage, compatibility with existing work processes and trialability. Locus of control (worker vs. contractor) was not related to adoption. Simple solutions faced fewer barriers to adoption than those rated as complex. Conclusions: Specific adoption characteristics can help predict the use of new ergonomic solutions in construction. Adoption of complex solutions must involve multiple stakeholders, more time, and shifts in culture or work systems. Am. J. Ind. Med. 60:295–305, 2017. © 2017 Wiley Periodicals, Inc.